The Role of Al-Mazari in East Africa 1870 - 1896 - Nibrass Kh. Jadaan; Musleh M. Abed (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
The research aims to highlight the role played by the Al-Mazari in East Africa, and to clarify the relationship between them and the rulers of Al-Busaid, especially in the period 1870-1896 AD, which was represented by the Al-Busaid rulers standing against the Al-Mazari in East Africa. As a result of this, the Mazari made several revolts against the rulers of Al-Busaid in order to gain independence and to form a rule of their own. Thus, Mubarak bin Rashid Al Mazrouei, the leader of the largest branch AL-Mazari, revolted against them and against the British authority that had established a company in East Africa. However, with British and German cooperation they were eliminated and surrendered in 1896 AD. The research dealt with four basic investigations ,the first topic focused on the relationship of Mazari’s with Sultan Barghash bin Sa'ad 1870-1885, and the second topic dealt with the British-German conflict over East Africa and the establishment of the British East Africa Company from 1886-1888 AD, while the third topic dealt with Sultan Khalifa and his relationship with Mubarak bin Rashid Al Mazrouei 1888-1890 AD. . As for the fourth and final topic, it includes the revolution of Mubarak bin Rashid Al Mazrouei against Britain, which eliminated their influence permanently in 1896 AD.